Morphological and biochemical repercussions of Toxoplasma gondii infection in a 3D human brain neurospheres model - Leite, Paulo Emilio Correa (2021)
Fil: Leite, Paulo Emilio Correa. Institute of Biophysics Carlos Chagas Filho; Brasil